KUALIFIKASI PUBLIK RELATION FRANK JEFKINS PERSPEKTIF ISLAM - Rezqi Wahyudi (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This paper aims to explain Frank Jefkins Public Relations qualifications in the Islamic perspective. This qualification is the ability to communicate that is relevant to the recommendations of the Qur'an using the principles of communication qaulan sadida, karima, baligha, ma'rufa, layyina and qaulan maysura as effective communication in building harmonious relationships among others. PR practitioners must also have the ability to organize that is able to manage the organization with management principles. Islam declares about management by maintaining the mandate of each delegation of tasks given and is able to close ranks together to gain great strength in problems solving. In addition, the ability to establish relationships with other people is also a determining factor for public relations practitioners, which is also explained in the Qur'an that humans are created in plurality but are encouraged to always be friendly and make a difference as a force. Integrity, as an ethical behavior of every human being in living is according to religious and state rules. While creativity is explained in Islam as a necessity, so humans must always use reason to think creatively in producing PR programs and solve problems.